Age–period–cohort analyses of obesity prevalence in US adults. (December 2016) - An, R.; Xiang, X.
Abstract: Objectives: Age–period–cohort analysis is a stream of methodologies that decompose the temporal trends for disease risk into three time scales—age, calendar year (period) and year of birth (cohort). This study conducted age–period–cohort analyses of obesity prevalence in US adults. Study design: Retrospective data analysis. Methods: We constructed regression models based on anthropometric data from the 1999–2012 National Health and Nutrition Examination Survey to correct for the self-reported height/weight in the 1984–2014 Behavioral Risk Factor Surveillance System (BRFSS). We estimated fixed-effects age–period–cohort models based on the BRFSS data for the overall adult sample ( n = 6, 093, 293) and by sex and race/ethnicity, adjusting for individual characteristics and the BRFSS survey design. Results: An inverted U-shaped age effect on obesity and a positive period effect characterized by over-time increase in obesity risk independent of age and cohort influences were identified in the overall sample and subgroups by sex and race/ethnicity. From 1984 to 2014, the adjusted obesity prevalence increased by 21.1 percentage points among US adults, and 20.9, 21.6, 21.0, 26.4 and 20.1 percentage points in men, women, non-Hispanic whites, African Americans and Hispanics, respectively. In contrast, no consistent evidence was found in support of the cohort effect—the adjusted obesity risk was comparable across birth cohorts after accounting for the age and period effects. Conclusions: Shifts in the age distribution and nationwide secular changes may have fuelled the obesity epidemic in the USA over the past decades. Reversing the obesity epidemic may require understanding of the nationwide changes over time that affect weight gain across all population subgroups and promoting universal changes to diet, physical activity and the obesogenic environment. Highlights: We conducted age–period–cohort analyses of obesity prevalence in US adults. We identified an inverted U-shaped age effect on obesity. We found a positive period effect characterized by over-time rise in obesity risk. In contrast, no consistent evidence was found in support of the cohort effect. Obesity risk was stable across birth cohorts controlling for age and period effects.